Adsorption of uranium (VI) from groundwater by silicon containing biochar supported iron oxide nanoparticle. (June 2021) - Sen, Kamalesh; Mishra, Debojyoti; Debnath, Priyanka; Mondal, Arghadip; Mondal, Naba Kumar
Abstract: Present work is highlighted on the removal of U(VI) through batch experiment, by varying the parameters such as pH, adsorbent contact time & dose, temperature, initial concentration. The SB@Fe was characterized by X-ray diffraction spectroscopy (XRD), Brunauer Emmett-Teller surface area (BETsurface ), Point Zero Charge (ZPC), Field Emission Scanning Electron Microscopy (FESEM), Energy-dispersive X-ray spectroscopy (XEDS), X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared (FT-IR). Adsorption equilibrium were explained through kinetics and isotherm model. The pseudo-second order kinetic and the Langmuir isotherm were comparatively the best fitted, with the highest adsorption capacity at pH 5.5 of 138.88 mg/g. The adsorption mechanism was ascribed by thermodynamics parameters, which recommended the process in terms of exothermic, spontaneous and large available of randomness. Finally, Box-Behnken Design (BBD) was used for optimization of U (VI) removal up to 99.813%. Therefore, the present study indicated that the silicon containing biochar supported iron oxide nanoparticle could be a promising adsorbent for decontamination of U(VI) from underground water. Graphical abstract: Unlabelled Image Highlights: Impregnation of iron nanoparticle in silicon containing biochar Significant improvement of uranium (VI) adsorption Adsorption capacity was recorded as 138.88 mg/g. Box-Behnken Design was used for optimization study.